Pathomorphological changes in the aborted and neonatal horses corpses due to equine rhinopneumonitis - Prapirnyi, V. (Scientific Progress & Innovations, 2022)
The equine rhinopneumonia virus continues to cause significant economic losses to the horse breeding industry of Ukraine, however, information on the morphological changes in foal carcasses due to rhinopneumonia is still fragmentary and requires systematization. The research was conducted based on two horse farms, the branches of SE "Konyarstvo Ukrainy", which are not well-off about viral rhinopneumonia of horses, and on the basis of the Lysychansk Interdistrict State Laboratory of the State Service of Ukraine for Food Safety and Consumer Protection. The objects of the study were the corpses of aborted and neonatal foals. Macroscopic changes in the corpses of neonatal and aborted foals were studied by the methods of pathoanatomical dissection in the lateral position with partial or complete evisceration of organs and the visual palpation method. The study aimed to find out the informativeness of the pathomorphological picture in foals with viral rhinopneumonia. It was established that the pathomorphological signs of rhinopneumonia in aborted and neonatal foals were similar. Macroscopic changes in foal corpses are characterized by hypotrophy, rickets; stagnant hyperemia and pulmonary edema, croupous pneumonitis; dilated cardiomyopathy; congestive venous hyperemia of the kidneys and brain; fibrinous polyserositis. During the histological examination of changes in the myocardium, kidneys, and liver, dystrophic and ischemic phenomena were revealed; in the small intestine – acute catarrhal and hemorrhagic duodenitis. Violations of the external structure of the carcass were observed in 28.6 % of the studied foals. Histological and macroscopic changes were observed, respectively, in the heart of neonates in 57.1 and 42.9 % of cases; in the small intestine – in 85.7 and 71.4 % of cases; in the lungs – in 100 and 85.7 % of cases; in the spleen – in 85.7 and 57.1 % of cases. The analysis of the localization of pathological anatomical changes in aborted foals revealed that they were determined in the cadaver architecture, larynx, trachea, lungs, liver, spleen, duodenum, and kidneys of most of the research subjects. The obtained new scientific data have applied value during complex diagnosis of rhinopneumonia in horses.